Explorative Study of Glass Ceiling Phenomenon as Causal Factors to Female Leader Deficit in Indonesia - Syaebani, Muhammad Irfan; Pitaloka, Dian Rezky Catur; Suhardjo, Harryanto; Ulpah, Maria (Faculty of Economics, Universitas Sriwijaya, 2025)
Women are under-represented in top management positions, with their participation declining as positions increase. This study investigates the role of the 'glass ceiling' in contributing to the deficit of female leadership in Indonesia. This study adopted a qualitative methodology using a phenomenological approach. The research data was collected using semi-structured, in-depth interviews. The data were analysed using four stages of coding: open coding, axial coding, selective coding, and process coding. The findings show that the glass ceiling phenomenon results from several barriers faced by female employees. These barriers are categorised into five types: situational/organisational, social role, person-centred, interactional, and human capital. In conclusion, women workers in Indonesia face invisible barriers in various situations. These include organisational and socio-cultural factors as well as gender issues. This phenomenon creates a glass ceiling which prevents the advancement of women into leadership roles, leading to a deficit of female leaders in Indonesia